Twisting magnetic field and multiple resonance mechanism in the solar neutrino problem - Guzzo, M. M.; Pulido, J. (Elsevier, 1993)
The magnetic moment solution to the solar neutrino problem is investigated in the context of a solar magnetic field with varying phase velocity on the transverse plane. This phase velocity is assumed to successively take values which are approximately proportional to the solar density, giving rise to the appearance of many resonances along the neutrino trajectory. We obtain a magnetic moment necessary for a neutrino reduction compatible with the experimental situation in the range (6-7)×10-13μB, an improvement by a factor of 4-6 relative to the one resonance case under the same field conditions. © 1993.